Synthesis of (+)-4-desoxypentenomycin and analogues - Supakeat Kambutong (2018)
A synthesis of (+)-4-desoxypentenomycin is reported here; it involves diastereoselective phenylsulfanylpropylation of an enolate anion derived from methyl (2R,5R,6R)-5,6-dimethoxy-5,6-dimethyl[1,4]dioxane-2-carboxylate, obtained from D-mannitol, and is followed by sulfide oxidation, intramolecular acylation of the a-sulfinyl carbanion, sulfoxide elimination, and hydrolysis. Straightforward access to substituted analogues of (+)-4-desoxy-pentenomycin was also demonstrated by means of Suzuki-Miyaura, Sonogashira, and Heck coupling reactions. © Georg Thieme Verlag Stuttgart.